2006
DOI: 10.1200/jco.2006.24.18_suppl.570
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine (X) and taxanes in patients (pts) with anthracycline-pretreated metastatic breast cancer (MBC): Sequential vs. combined therapy results from a MOSG randomized phase III trial

Abstract: 570 Introduction: Capecitabine (Xeloda [X]) shows synergy with taxanes and adding X to docetaxel (T) extends overall survival (OS), response rate (RR) and progression free-survival (PFS) beyond T alone. Sequential single-agent therapy could confer convenience benefits and may be more appropriate than combination chemotherapy for some pts. Methods: Pts with anthracycline-pretreated MBC received 3-weekly cycles of 1 of the following regimens: X→taxane (X 1250mg/m2 bid d1–14, followed after progression (PD) by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…Eight other small phase II or phase III studies comparing sequential versus combination approaches showed different results. Two (15,16) showed a better response rate in the combination arm, whereas others showed similar efficacy of both approaches (17)(18)(19)(20)(21)(22). Safety profile was better in the sequential arm in three of these eight trials (17)(18)(19), whereas two trials showed similar toxicity (15,20) and in three hematological toxicity was higher in the sequential arm (16,21,22).…”
Section: Discussionmentioning
confidence: 96%
“…Eight other small phase II or phase III studies comparing sequential versus combination approaches showed different results. Two (15,16) showed a better response rate in the combination arm, whereas others showed similar efficacy of both approaches (17)(18)(19)(20)(21)(22). Safety profile was better in the sequential arm in three of these eight trials (17)(18)(19), whereas two trials showed similar toxicity (15,20) and in three hematological toxicity was higher in the sequential arm (16,21,22).…”
Section: Discussionmentioning
confidence: 96%
“…[16][17][18] Prospective randomized studies often have explored reduced-dose capecitabine in doublets with other cytotoxic agents, making these data difficult to interpret for the impact of the modified capecitabine dose alone. 19,[26][27][28] An additional complication arises from data indicating that body surface area-based dosing may not be ideal. 29 We developed a method to predict the optimal dosing of chemotherapy and applied it specifically to capecitabine.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Several studies have explored alternative capecitabine doses and schedules as monotherapy and in capecitabine-based combinations for both breast and colorectal cancers. [16][17][18][19][20] However, these dose modifications were derived empirically with unclear impact on patient outcome.…”
mentioning
confidence: 99%
“…resulted in higher response rates and time to progression, they have not improved overall survival or quality of life. 5,6 In addition, the absence of planned crossover in most studies meant that not all patients in the sequential groups received the second agent, a situation that 25 21-day cycle (n=230) HR = hazard ratio; CI = confidence interval; PFS = progression-free survival; TTP = time to progression; HER2 = human epidermal growth factor receptor-2. a Primary end point.…”
Section: Combination Versus Single-agent Sequential Chemotherapymentioning
confidence: 99%